PENINGKATKAN KEMAMPUAN BAHASA EKSPRESIF MELALUI KEGIATAN DONGENG MENGGUNAKAN MEDIA BONEKA TANGAN PADA ANAK USIA 5-6 TAHUN DI PAUD PRIMA SAKINAH - Putri Mega; Astuti Darmiyanti; Feronica Eka Putri (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
This classroom action research aims to improve expressive language skills in children aged 5-6 years by using hand puppet media in group B at Prima Sakinah PAUD. This research is a class action research (CAR). . This method was carried out in four stages, namely planning, action, implementation, and reflection. The research subject was group B of Prima Sakinah PAUD, which consisted of 10 children. Data collection methods used are observation and documentation. The success indicator set is that 75% of 10 children achieve expressive language skills in children aged 5-6 years. This research was conducted in two cycles. Cycle I was held in 6 meetings and Cycle II was held in 4 meetings. The results showed that there was an increase in the expressive language skills of children aged 5-6 years using the media "hand puppets". improved by using hand puppet learning media. By proving the results of the average percentage in the pre-action conditions of 13.9% after the first cycle increased by 65.6% then after the second cycle increased by 89.4%.